Ethnomethodological conversation analysis and the study of assemblages - Raudaskoski, Pirkko (Frontiers in Sociology, 2023)
The material turn where phenomena are treated as complex material and embodied processes has challenged traditional social scientific and humanistic research approaches. Both individual and community are rejected as a starting point for theorizing what is going on in societies and cultures. In fact, all dichotomies are deemed suspect, and the research focus lies heavily on actual practices. The concept heterogenous assemblage is used in at least two strands of the material turn with slightly different takes on the entangled nature of practices. These are actor-network theory, ANT (cf. STS, e.g., Callon, Latour, Law) and new materialism(s) (cf. process philosophy, e.g., Deleuze, Guattari). Both can be placed under the umbrella term sociomaterialism. In their analysis of concrete phenomena, Deleuzian assemblages tend to focus on embodied sensations (affect) that have rhizomatic threads of connection, whereas ANT’s assemblages include how heterogenous entities (actants) stabilize certain practices. With a revised understanding of how the word works (ontology), the usefulness of traditional research methods (epistemology) to study concrete phenomena has also been questioned. Margaret Wetherell has suggested that affect assemblages can be analyzed as observable social practices, giving an EMCA-based study as an illustrative example. The question is whether both new materialist intensities (cf. certain approaches in psychology) and ANT’s connections to other people, places, and practices (e.g., in organization studies) could be analyzed with an EMCA approach. This paper acknowledges the existing possibilities EMCA offers to analyze heterogenous assemblages as situated interactional and material entanglements and enlarges the repertoire by focusing on 1) how the material specifics can make the EMCA “why that now” analysis connect to larger assemblages than the local accomplishment of action, and 2) how observable orientations to phenomena outside of the situation can be treated as an assemblic activity. It will do this with 1) Goodwin’s concept lamination that enlarges the strictly situation-bound contextual configuration analysis to the cultural-historical formations through the use of material tools, and with 2) mentionings that combine MCA and Cooren’s interest in non-human (material) actors. In other words, the well-known sociomaterial concept material-discursive is translated into two analytical possibilities to study sociomaterial heterogenous assemblages.